1998
DOI: 10.1128/jb.180.4.767-772.1998
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Anion Balance during Inhibition of Growth ofEscherichia coliby Weak Acids

Abstract: During inhibition of cell growth by weak acids, there is substantial accumulation of the weak acid anions in the cytoplasm. This study was undertaken to determine the impact of anion accumulation on cellular pools. At pH 6, growth in the presence of 8 mM acetate led to an internal pool of greater than 240 mM acetate anion and resulted in reduced levels of glutamate in the cell, but there were no significant changes in K+ and Na+ levels. At low osmolarity, the change in the glutamate pool compensated for only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
209
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(221 citation statements)
references
References 19 publications
10
209
1
1
Order By: Relevance
“…Acetate and related short-chain fatty acids are abundant fermentation products in the human large intestine and can be present at concentrations above 100 mM (Cummings et al, 1987). Acetate anion is known to accumulate in the bacterial cytoplasm and to temporarily disturb metabolism (Roe et al, 1998;Roe et al, 2002). The current data suggest that the unusual salt-sensitivity of the ribosomal promoters allows cellular resources to be conserved while the cell adapts to these perturbations by ensuring that bulk transcription is inhibited during this time.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Acetate and related short-chain fatty acids are abundant fermentation products in the human large intestine and can be present at concentrations above 100 mM (Cummings et al, 1987). Acetate anion is known to accumulate in the bacterial cytoplasm and to temporarily disturb metabolism (Roe et al, 1998;Roe et al, 2002). The current data suggest that the unusual salt-sensitivity of the ribosomal promoters allows cellular resources to be conserved while the cell adapts to these perturbations by ensuring that bulk transcription is inhibited during this time.…”
Section: Discussionmentioning
confidence: 76%
“…The growth behavior ( Figure 2) is similar to that seen with salt shock; there is an immediate halt, followed by a lag, in turn followed by resumed growth. In this case, the lag is much longer likely due to the toxic effects of imported acetate (Roe et al, 1998). Preribosomal RNA analysis 5 min after addition (broken arrow) shows that potassium acetate also leads to a severe inhibition of ribosomal transcription (Figure 2, inset lane 2 compared to the lane 1 control).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…the concentration of 2,4-D and Clions in cultures of B. cepacia strain 2a) and assuming an average intracellular volume of~1 ¥ 10 -15 litres (Neidhardt et al, 1990), it is possible to speculate that the intracellular Clion concentration would have already risen to approximately 650 mM after 2 h of commencing utilization of 2,4-D. It has been reported that an intracellular chloride concentration of up to 160 mM can be tolerated by E. coli by the release of glutamate and other anions (Roe et al, 1998) but 650 mM would be far beyond that limit. The consequence would be to induce either cell stasis or death, which is our observation for a B. cepacia strain 2a bearing mutant possessing a closed-channel protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA concentrations, however, are approximately 40% lower in the distal compared with the proximal colon (Macfarlane et al 1992). The impact of each of the three main fermentation products differs, but these weak acids all act to lower the colonic pH and thus may prevent the growth of potentially pathogenic bacteria, particularly Enterobacteraciae, which are generally sensitive to low pH (Roe et al 1998;Hirshfield et al 2003).…”
Section: Bacterial Fermentationmentioning
confidence: 99%